Daylighting for energy conservation in the tropics: a study on the influences of window configurations and shading devices. (3rd August 2009) - Tanachaikhan, Lerdlekha; Kumar, S.
This paper presents the results of an analysis of window design for daylighting in the tropics to benefit from light gain while minimising the increase of cooling load due to heat gain. The influences of window orientation, window area, window height and shading devices on daylight availability, supplementary lighting, cooling load and possible savings were evaluated for tropical climate conditions. The results indicate that Bangkok has high availability of daylight. Also, electric power demand and savings in lighting and cooling depends on season and window configuration. The possible savings in lighting could be up to 99% and the total electric power required could decrease up to 70% for various window configurations as compared to no daylight applied conditions. For shaded windows, the overall savings from daylighting could be more than 13 W/m² or 52% of electric power reduction compared with unshaded ones.